The Effect of Thyroid Nodule Size and Characteristics on the Accuracy of Fine-Needle Aspiration Biopsy and the Risk of Malignancy - Mehmet Alperen Avcı; Can Akgün; Mustafa Gün; Selim Tamam; Meltem Türk (Hitit Medical Journal)

(untitled)
Objective: Ultrasound evaluation of nodule characteristics and FNAB is a simple, cost-effective method. However, its reliability in large nodules is controversial. This study aims to examine the impact of thyroid nodule size and characteristics on malignancy risk and FNAB accuracy as evaluated by ultrasound. Material and Method: This retrospective study included 522 patients who underwent thyroidectomy between January 1, 2020, and January 1, 2024. The data included the patients’ age, gender, preoperative thyroid ultrasound findings, preoperative FNAB pathology findings, operation notes, and postoperative pathology results colleected from hospital archives. Kruskal-Wallis Variance Analysis, ROC (Receiver Operating Characteristics) curve analysis, Bonferroni Corrected Mann-Whitney U Test, Chi-Square Tests, were used at statistical analysis. Results: The median age was 49.45 years. The threshold value for nodule size in the X plane was 27 mm (p27 mm.